(i) Use the fundamental theorem of algebra (or Vieta's formulas).
[tex]x^2 + px + q = (x + 3) (x - 5) = x^2 - 2x - 15 \\\\ \implies \boxed{p = -2 \text{ and } q = -15}[/tex]
(ii) By completing the square,
[tex]x^2 + px + q + r = \left(x + \dfrac p2\right)^2 + q + r - \dfrac{p^2}4[/tex]
Then using the values of [tex]p,q[/tex], we have
[tex](x - 1)^2 - 15 + r - 1 = 0 \implies (x - 1)^2 = 16 - r[/tex]
Observe that if [tex]\boxed{r=16}[/tex], then the quadratic has two roots at [tex]x=1[/tex], since this would give
[tex](x - 1)^2 = 0[/tex]